The effect of post-traumatic growth on recovery in liver transplant recipients - Harmanci, Pinar; Bulbuloglu, Semra (Frontiers in Psychiatry, 2023)
Aim: In our study, we examined the effect of post-traumatic growth on recovery in liver transplant recipients in the post-transplant period. Method: This research was performed as a descriptive and cross-sectional study with the participation of 218 patients who had liver transplantation at the liver transplant institute of a research and training hospital. The personal information form, the Post-Traumatic Growth Inventory, and the Recovery Assessment Scale were used in the data collection process. The Statistical Package for Social Science 25.0 was utilized in the data analysis process. Findings: In the research, of all participant liver transplant recipients, 67.8% were aged 45-64 years, 34.4% had incomes below expenses, and 91.7% had living donor liver transplantation. Besides, it was found that participants who had living donor liver transplantation obtained higher mean scores from both the Post-Traumatic Growth Inventory and the Recovery Assessment Scale than participants who had cadaveric donor liver transplantation, and likewise, participants who had past surgery experiences obtained higher mean scores from both the Post-Traumatic Growth Inventory and the Recovery Assessment Scale than participants who had no past surgery experience (p<0.05). Moreover, there was a statistically significant positive linear relationship between participant liver transplant recipients’ Post-Traumatic Growth Inventory and Recovery Assessment Scale scores. Conclusion: Post-traumatic growth supports recovery. Also, social support and a good economic situation are other parameters that promote recovery. In the two-year process during which the treatment is intensively applied to liver transplant recipients following the transplantation surgery, it is important to enable patients to find more meaning in life and to find solutions that facilitate recovery. Keywords: Liver recipients, Post-traumatic growth, Recovery, Transplantation